Special considerations of antibiotic prescription in the geriatric population. (January 2015) - Beckett, C.L.; Harbarth, S.; Huttner, B.
Abstract: Infectious diseases pose a major challenge in the elderly for two reasons: on the one hand the susceptibility to infection increases with age and when infections occur they often present atypically—on the other hand diagnostic uncertainty is much more pronounced in the geriatric population. Reconciling the opposing aspects of optimizing patient outcomes while avoiding antibiotic overuse requires significant expertise that can be provided by an infectious diseases consultant. In addition, geriatric facilities are reservoirs for multidrug-resistant organisms and other nosocomial pathogens, and infectious diseases consultants also play a vital role in assuring appropriate infection control measures. In this review we outline the challenges of diagnosis and management of infectious diseases in the elderly, and discuss the importance of appropriate antibiotic use in the elderly in order to demonstrate the value of the infectious diseases consultant in this special setting.